Functional-behavioral characteristics of information technology formation of merchantability company policy - Малай, Антон Михайлович; Лисицкий, Василий Лаврентиевич (Eastern-European Journal of Enterprise Technologies, 2012)
The functional-behavioral characteristics of science-based information technology company formation commodity policy functioning in a competitive environment are considered